PENGARUH LATIHAN SERVIS ATAS TERHADAP HASIL RESERVIS ATLET SEPAK TAKRAW BBTC KOTA PADANG - Dini Yati, Riza; Putra, Yogi Arnaldo; Padli; Setiawan, Yogi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of top service training on the re-service ability of sepak takraw athletes at BBTC Padang City. This research employed a quasi-experimental method using a one-group pretest-posttest design. The population consisted of 7 athletes and all participants were selected as research samples through total sampling. Data were collected using a re-service skill test and analyzed using paired sample t-test. The findings revealed an increase in the mean score of re-service ability from 20.0 in the pretest to 27.3 in the posttest. The statistical analysis showed a mean difference of -7.28571, t-value of -12.885, and significance value of 0.000 (p < 0.05). These results indicate that top service training significantly improved the re-service ability of sepak takraw athletes. Therefore, top service training can be recommended as an effective training method to improve re-service performance in sepak takraw players.